Thermodynamic assessment of oxide system In2O3-SnO2-ZnO - T. Jantzen; K. Hack; E. Yazhenskikh; M. Müller (Chimica Techno Acta)
The In2O3-SnO2-ZnO system is of special interest for applications as transparent conducting oxides and also transparent semiconductors. In the present work, a thermodynamic assessment for this system is discussed using all available experimental data on phase equilibria and thermodynamic properties. All sub-systems including elemental combinations were considered in order to generate a self-consistent Gibbs energy dataset for further calculation and prediction of thermodynamic properties of the system. The modified associate species model was used for the description of the liquid phase. Particular attention was given to two significant solid solution phases: Spinel with the formula Zn(2-x)Sn(1-x)In2xO4 based on Zn2SnO4 and Bixbyite based on In2O3 and extending strongly toward the SnZnO3 composition according to the formula In(2‑2x)SnxZnxO3. In addition to the component oxides, nine quasi-binary compounds located in the In2O3-ZnO binary subsystem have also been included in the database as stoichiometric phases.